Absorption of lefradafiban from different sites of the gastrointestinal tract - Drewe, Jürgen (Blackwell Science Inc, 2000)
AIMS: Fibrinogen receptor antagonists show a close relationship between plasma concentrations and inhibitory effect. Optimal efficacy at an acceptable bleeding risk requires low inter- and intrasubject variability on low peak trough fluctuation in receptor occupancy and therefore also of plasma concentrations. Therefore, the enteral absorption of lefradafiban, an orally available fibrinogen receptor antagonist prodrug, was investigated after local administrations to different sites of the gastrointestinal tract in order to investigate the feasibility of an oral extended release formulation. METHODS: Twelve healthy male subjects received in a randomised, open-labelled, four-period crossover trial four consecutive administrations of lefradafiban: 1. orally; 2. administration into the jejunum, 3. administration into the lower jejunum/ileum (300 cm distally to the teeth), and 4. administration into the lumen of the sigmoid region (30 cm proximally to the anus). Local intestinal administrations were performed through a gastrointestinal tube. RESULTS: Compared with oral administration, ratios [mean (two-sided 90% confidence intervals)] of maximum drug plasma concentrations and AUC(0,24 h) of fradafiban were 1.05 (0.80,1.39) and 1.06 (0.85,1.31) after jejunal, 0.98 (0.75,1.30) and 0.98 (0.79,1.21) after ileal, 0.52 (0.39,0.69) and 0.68 (0.55,0.85) after colonic administration. Urinary excretion of fradafiban was about 16% of the dose after oral, jejunal and ileal applications whereas after rectal administration about 11% were excreted. CONCLUSIONS: Lefradafiban is absorbed throughout the entire gastrointestinal tract. Therefore, an extended release formulation seems to be feasible with regard to bioavailability.